2017
DOI: 10.1073/pnas.1713969114
|View full text |Cite
|
Sign up to set email alerts
|

TrkB neurotrophic activities are blocked by α-synuclein, triggering dopaminergic cell death in Parkinson’s disease

Abstract: BDNF/TrkB neurotrophic signaling is essential for dopaminergic neuronal survival, and the activities are reduced in the substantial nigra (SN) of Parkinson's disease (PD). However, whether α-Syn (alpha-synuclein) aggregation, a hallmark in the remaining SN neurons in PD, accounts for the neurotrophic inhibition remains elusive. Here we show that α-Syn selectively interacts with TrkB receptors and inhibits BDNF/TrkB signaling, leading to dopaminergic neuronal death. α-Syn binds to the kinase domain on TrkB, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 34 publications
4
78
0
2
Order By: Relevance
“…We observed the appearance of hyperphosphorylated, AEP-cleaved, and Gallyas-Braak-positive forms of Tau in the EC, HC, and Cx of both transgenic strains following intra-LC infusion of mCherry + Tau virus. Importantly, generating the neurotoxic DA metabolite DOPAL in PD (21,45), and here we show that NE metabolism into DOPEGAL by MAO-A in the progression of AD-like pathology. Combined, these results support our model that DA metabolism into DOPAL and MAO-A-mediated conversion of NE into DOPEGAL induce α-synuclein toxicity in SN and Tau toxicity in LC, respectively, leading to the selective vulnerability of catecholamine neurons in PD and AD (Figure 12).…”
Section: Discussionsupporting
confidence: 60%
“…We observed the appearance of hyperphosphorylated, AEP-cleaved, and Gallyas-Braak-positive forms of Tau in the EC, HC, and Cx of both transgenic strains following intra-LC infusion of mCherry + Tau virus. Importantly, generating the neurotoxic DA metabolite DOPAL in PD (21,45), and here we show that NE metabolism into DOPEGAL by MAO-A in the progression of AD-like pathology. Combined, these results support our model that DA metabolism into DOPAL and MAO-A-mediated conversion of NE into DOPEGAL induce α-synuclein toxicity in SN and Tau toxicity in LC, respectively, leading to the selective vulnerability of catecholamine neurons in PD and AD (Figure 12).…”
Section: Discussionsupporting
confidence: 60%
“…For instance, DOPEGAL and MAO-A levels are elevated 2.8- and 3.6-fold in AD LC neuronal cell bodies compared to controls (24), while MAO-B expression and activity are higher in multiple brain regions and cell types in AD (41, 42). While both MAO-A and MAO-B were capable of increasing AEP activity, Tau N368 cleavage, and cell death in our experiments, we favor MAO-A as the main driver of DOPEGAL production in vivo , with MAO-B playing a greater role generating the neurotoxic DA metabolite DOPAL in PD (21, 43) (Figure 7); that said, confirming this hypothesis will require additional experiments.…”
Section: Discussionsupporting
confidence: 47%
“…Decreased BDNF concentration in serum and brain is accompanied by an increase in degeneration of dopaminergic neurons in PD, which leads to movement disorders, cognitive deficit, and mental disorders [63][64][65][66] and also correlates with memory impairment in AD [67,68]. There are data indicating that a decrease in BDNF levels in PD may contribute to overexpression of alpha-synuclein (ASN) and inhibition of dopamine (DA) synthesis [69][70][71]. Moreover, it was reported that ASN overexpression downregulated BDNF transcription and impaired BDNF trafficking in neurons [53].…”
Section: Role Of Bdnf In Neurodegeneration and Neuroregenerationmentioning
confidence: 99%